DEMAN FOR CHEMICAL FERTILIZER OF THE TECHNICAL IRRIGATION PADDY IN EAST OGAN KOMERING ULU - Munajat Munajat (Universitas Islam Indonesia, 2010)
This research investigates factors that influence demand for chemical fertilizer of the technical irrigationpaddy in East Ogan Komering Ulu Regency. Using a multiple regression analysis, the resultshows that the significant factors influencing the urea fertilizer demand are the price of urea fertilizerand the previous paddy production. It also finds that the price of paddy and total member offamily do not significantly influence the fertilizer. Meanwhile the significant factors that influencethe SP 18 fertilizer demand are the price of SP 18 fertilizer, the price of paddy and the previouspaddy production.Keywords: Urea fertilizer demand, SP 18 fertilizer demand, fertilizer subsidyJEL classification numbers: O13, 018